PERAN KELOMPOK TANI HUTAN (KTH) SEJAHTERA BERSAMA TERHADAP PROGRAM KEMITRAAN KONSERVASI DALAM RANGKA PEMULIHAN EKOSISTEM PADA ZONA REHABILITASI DI KAWASAN TAMAN NASIONAL KERINCI SEBLAT (TNKS) - Soraya, Elmitha Tri; Wilis, Ratna (JURNAL BUANA, 2024)
This study aims to determine the form of activity, the role of KTH Sejahtera Bersama, and the benefits of ecosystem restoration activities in the rehabilitation zone in the TNKS area, SPTN Wil.IV Sangir, Sungai Lambai Resort, South Solok Regency. This research focuses on the role of institutional strengthening and group capacity, in planting and maintaining ecosystem restoration plants on arable land which is a rehabilitation zone in the TNKS area.This type of research is a Mixed Methods using a qualitative approach combined with quantitative.The results of the study show (1) The form of ecosystem restoration activities on KTH Sejahtera Bersama's land has been carried out properly based on the Annual Activity Plan (RKT). (2) The role of KTH Sejahtera Bersama in institutional strengthening and group capacity was obtained by a high level role category, in intensive planting activities it was in accordance with the TNKS directives, and plant maintenance activities had not been carried out properly due to several factors on plants, the results of identification samples of plant seeds that life is classified as low with a percentage of less than 50%. (3) Benefits for individuals from KTH Sejahtera Bersama include legality of cultivating land, assistance in the form of work equipment, fertilizers, wages for picking seeds, wages for clearing land, fees for stakes, fees for planting, and additional income from crops on arable land and yields of recovery crops later ecosystem. The benefits for the group are exchanging information, experience, and support for extension activities or information from the TNKS, as a forum for cooperation in the planning, implementation, utilization and evaluation stages.